5x/6-(3-x)/8=4x+3/12

Simple and best practice solution for 5x/6-(3-x)/8=4x+3/12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x/6-(3-x)/8=4x+3/12 equation:


x in (-oo:+oo)

(5*x)/6-((3-x)/8) = 4*x+3/12 // - 4*x+3/12

(5*x)/6-((3-x)/8)-(4*x)-(3/12) = 0

(5*x)/6-((3-x)/8)-4*x-1/4 = 0

(-1*(3-x))/8+(5*x)/6-4*x-1/4 = 0

(-1*4*6*(3-x))/(4*6*8)+(4*5*8*x)/(4*6*8)+(-4*4*6*8*x)/(4*6*8)+(-1*6*8)/(4*6*8) = 0

4*5*8*x-1*4*6*(3-x)-4*4*6*8*x-1*6*8 = 0

184*x-768*x-72-48 = 0

-584*x-72-48 = 0

-584*x-120 = 0

(-584*x-120)/(4*6*8) = 0

(-584*x-120)/(4*6*8) = 0 // * 4*6*8

-584*x-120 = 0

-584*x-120 = 0 // + 120

-584*x = 120 // : -584

x = 120/(-584)

x = -15/73

x = -15/73

See similar equations:

| 2xsquared+12.5=0 | | 1=2-3v+2v | | 33=-8x-31 | | 6(2w+v)-4(2v+1w)=0 | | -3/8p=-9 | | .6x^2=3.6x+.6 | | 5x+3=4x-14 | | 1/2(3t-7)=t/4+7/4 | | -(2x-5)-(2x-6)+3=-4(x-1)-(3x+5)+3 | | 6p+4p+.75+3p= | | -73+8x=71 | | 3(m-z)+5(2m-z)=0 | | 7p^2=-18p-8 | | 12x+15(312-x)=13*312 | | 33x^2+39x=0 | | -86=-2(3n+1)-6n | | -83=10x+97 | | 7y+(5y+5)= | | 8x+5-6(x+1)=7x+3 | | 2y+3(y-9)=-3(3y-18)-y | | -7(1+3x)=161 | | 1=5p-2-2 | | (c)8-10=3c+5 | | 5-[2(-4)-1]=10-x | | 2x+20=46 | | -212=-2-6(5v-2) | | 3(4-7)=-21+12z | | 5-[(-4)-1]=10-x | | x^3+2x^3=72 | | v^2-16-6v=0 | | -4y-1(5y+6)=-7y+3 | | -2(8n+1)-4(n+5)=-2 |

Equations solver categories